In the Shadow of the Black Beast : African American Masculinity in the Harlem and Southern Renaissances - Leiter, Andrew B., 1972- (Book collections on Project MUSE., 2010)
Andrew B. Leiter presents the first book-length study of the sexually violent African American man, or "black beast," as a composite literary phenomenon. According to Leiter, the black beast theme served as a fundamental link between the Harlem and Southern Renaissances, with writers from both movements exploring its psychological, cultural, and social ramifications. Indeed, Leiter asserts that the two groups consciously engaged one another's work as they struggled to define roles for black masculinity in a society that viewed the black beast as the raison d'être for segregation. In the Shadow.